(untitled) (Research, Society and Development, 2021)
Objectives: This study aims to analyze the integrality and the importance of the qualification of health professionals, identifying the current situation of professional training for the care of patients with ASD in Brazil, as well as the problems faced in this process. Methodology: This research consists of investigation through questionnaires, quantified and interpreted statistically using Microsoft Excel software, which sought to be based on the Research Project Muito Além do Autismo. Results and discussion: The results show that 59% of the interviewees, during their professional training, had some contact with the topic of autism. Furthermore, in the questionnaire regarding the depth of information covered on the topic during graduation, 27% responded that the topic was mentioned in a superficial way, this shows that there is a need for further exploration of autism in educational institutions. Conclusion: Currently, in the qualification of health professionals, this topic is superficially addressed in undergraduate courses, making the diagnosis and early intervention of the disorder difficult.